2000
DOI: 10.1111/j.1460-9592.2000.ab01q.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of paediatric trauma admissions at the Royal London Hospital (February 98 to February 99)

Abstract: An Intervention Score (I/S) was designed: 1 = no interventions and discharged day of surgery; 2 = no interventions but overnight stay in hospital; 3 = minor interventions (O 2 therapy, airway manipulation or arti®cial airway) and discharged on day of surgery; 4 = minor interventions but stayed overnight; 5 = major interventions (IPPV, reintubation, cardiac arrest or ICU admission). The I/S was further collapsed into two categories; 1 and 2 = nil interventions and 3, 4 and 5 = interventions. Results The charts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…While it is difficult to define the ideal time interval between ER arrival and emergency surgery, Western trauma centers generally define it as within 2 hours. A study of the Royal London Hospital found that the mean duration from ER arrival to emergency surgery was 56 minutes for blunt trauma and 37 minutes for penetrating trauma [ 20 ]. Another study using American College of Surgeons audit filters found that performance of laparotomy more than 2 hours after admission resulted in increased mortality and longer ICU and hospital stay [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…While it is difficult to define the ideal time interval between ER arrival and emergency surgery, Western trauma centers generally define it as within 2 hours. A study of the Royal London Hospital found that the mean duration from ER arrival to emergency surgery was 56 minutes for blunt trauma and 37 minutes for penetrating trauma [ 20 ]. Another study using American College of Surgeons audit filters found that performance of laparotomy more than 2 hours after admission resulted in increased mortality and longer ICU and hospital stay [ 21 ].…”
Section: Discussionmentioning
confidence: 99%